THU0387 Effects of Blisibimod, An Inhibitor of B Cell Activating Factor, On Patient Reported Outcomes and Disease Activity in Patients with Systemic Lupus Erythematosus. (9th June 2015) - Petri, M.; Martin, R.S.; Hislop, C.; Scheinberg, M.A.; Furie, R.A.
Abstract : Background: Blisibimod (A-623, AMG 623), a potent and selective inhibitor of B-cell activating factor (BAFF), was evaluated in the phase 2b clinical trial PEARL-SC (NCT01162681 ) in patients with systemic lupus erythematosus (SLE). Effects of blisibimod on disease activity and safety were reported previously [1]. Objectives: To conduct secondary endpoint analyses of the effects of subcutaneously-administered blisibimod on patient-reported outcomes from the PEARL-SC trial. Methods: 547 SLE patients who met the ACR classification criteria, had anti-double-stranded DNA or anti-nuclear antibodies, and SELENA-SLEDAI score ≥6 at baseline, were randomized in the PEARL-SC study 1:1 to receive placebo or blisibimod administered at 1 of 3 dose levels, 100 mg weekly (QW), 200 mg QW, or 200 mg every 4 weeks for up to 52 weeks (with a median of 37 weeks) or until the last subject completed 6 months of study drug therapy. Patient self-reported outcomes were evaluated using the Functional Assessment of Chronic Illness Therapy (FACIT)-Fatigue scale, and disease activity was evaluated utilizing both SELENA-SLEDAI and BILAG. Results: Significant improvements in measures of disease activity in subjects with severe disease (defined as baseline SELENA-SLEDAI score≥10 and receiving steroids), especially at the highest blisibimod dose of 200mg QW, were reported previously [1]. Approximately 76% of subjects had SELENA-SLEDAI musculoskeletal involvement at enrollment, and 89% of subjects had mucocutaneous involvement. At Week 24, approximately 12% and 39% of subjects randomized to the 200mg QW blisibimod arm had musculoskeletal or mucocutaneous organ involvement, compared with approximately 15% and 42% respectively in the placebo arm (p<0.2 to p<0.05 across manifestations evaluated over Weeks 12 through 24). Improvements in self-reported fatigue were observed amongst subjects randomized to blisibimod based on the FACIT-Fatigue scale, especially in the 200mg QW group (N=80) where favorable effects of blisibimod compared with placebo were observed as early as Week 8, and a mean 6.9-point improvement from baseline was reported at Week 24 compared to 4.4 with placebo (N=229). These effects meet the criteria for minimal clinically-important improvement difference of 5.9 defined by Goligher and colleagues [2] for patients with SLE. Conclusions: Fatigue remains a debilitating manifestation of lupus. In this trial, blisibimod showed a tendency toward improved mucocutaneous and musculoskeletal disease activity as well as patient self-reported fatigue. These data support further evaluation of blisibimod in patients with SLE. References: Furie RA, Leon G, Thomas M, Petri MA, et al. A phase 2, randomised, placebo-controlled clinical trial of blisibimod, an inhibitor of B cell activating factor, in patients with moderate-to-severe systemic lupus erythematosus, the PEARL-SC study. Ann Rheum Dis. 2014. Goligher EC, Pouchot J, Brant R, Kherani RB et al. Minimal clinically important difference for 7 measures of fatigue in patients with systemic lupus erythematosus. J Rheumatol. 2008;35(4):635-42. Acknowledgements: We wish to thank all of the patients, Investigators and clinical teams involved in the PEARl-SC trial. Disclosure of Interest: M. Petri Consultant for: Anthera Pharmaceuticals, R. Martin Shareholder of: Anthera Pharmaceuticals, Employee of: Anthera Pharmaceuticals, C. Hislop Shareholder of: Anthera Pharmaceuticals, Employee of: Anthera Pharmaceuticals, M. Scheinberg: None declared, R. Furie Consultant for: Anthera Pharmaceuticals